2018
DOI: 10.1038/s41423-018-0087-y
|View full text |Cite
|
Sign up to set email alerts
|

In drug-induced, immune-mediated hepatitis, interleukin-33 reduces hepatitis and improves survival independently and as a consequence of FoxP3+ T-cell activity

Abstract: Immune-mediated, drug-induced hepatitis is a rare complication of halogenated volatile anesthetic administration. IL-4-regulated Th2-polarized reactions initiate this type and other types of hepatitis, while the mechanisms that regulate the severity remain elusive. IL-33 is an innate, IL-4-inducing, Th2-polarizing cytokine that has been detected in patients with liver failure and has been associated with upregulated ST2+Foxp3+CD4+CD25+ T cells; however, roles for IL-33 in drug-induced hepatitis are unclear. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…Our recent studies support the notion that IL-33, is protective in male mice with NASH and possibly in the associated cardiomyopathy [20]. Our prior investigations also support anti-inflammatory roles for IL-33 in drug-induced hepatitis via FoxP3þ Tregs and IL-10 [40]. However, IL-33 activates numerous signaling pathways by binding to ST2L, expressed on various cells [41].…”
Section: A Proposed Mechanism Of Crosstalk Between the Hepatic And Ca...supporting
confidence: 84%
“…Our recent studies support the notion that IL-33, is protective in male mice with NASH and possibly in the associated cardiomyopathy [20]. Our prior investigations also support anti-inflammatory roles for IL-33 in drug-induced hepatitis via FoxP3þ Tregs and IL-10 [40]. However, IL-33 activates numerous signaling pathways by binding to ST2L, expressed on various cells [41].…”
Section: A Proposed Mechanism Of Crosstalk Between the Hepatic And Ca...supporting
confidence: 84%
“…The Tregs negatively regulate effective T cell immune responses via the production of immunosuppressive cytokines (including IL-10 and TGF-β) during chronic infection and are considered to be a potential target for the treatment of patients with CHB (7). Through upregulated Tregs, IL-33 exerts a negative effect on CD4 + T cell proliferation and alleviates hepatitis (76). Similarly, it was found that Tregs orchestrate CD8 + T cell exhaustion by engaging the PD-1 inhibitory pathway during LCMV infection (77).…”
Section: The Adaptive Immune Tolerance Mechanismsmentioning
confidence: 99%
“…IL4 is a well-known Th2-promoting cytokine. 44,45 Paradoxically, IL4 from iNKT cells promoted STAT6 phosphorylation and IL12 production in DCs and enhanced iNKT cell-mediated Th1 responses (Fig. 2).…”
Section: Discussionmentioning
confidence: 93%